Foreign Exchange Intervention in Developing and Transition Economies : Results of a Survey - Canales Kriljenko, Jorge (IMF Working Papers; Working Paper ;, 2003)
Based on evidence obtained from the IMF's 2001 Survey on Foreign Exchange Market Organization, the author argues that, for several reasons, some central banks in developing and transition economies may be able to conduct foreign exchange intervention more effectively than the central banks of developed countries issuing the major international currencies. First, these central banks do not always fully sterilize their foreign exchange interventions. In addition, they issue regulations and conduct their foreign exchange operations in a way that increases the central bank's information advantage and the size of their foreign exchange intervention relative to foreign exchange market turnover. Some of the central banks also use moral suasion to support their foreign exchange interventions.